2019
DOI: 10.1590/1981-6723.05119
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics and mass transfer properties in the drying of thistle flower

Abstract: Thistle flowers, and particularly their stigmas, are used to coagulate milk in the production of a number of traditional Portuguese cheeses due to their high milk-clotting activity provided by the high content of aspartic proteases. The aim of the present work was to determine the mass transfer properties of thistle flower under different drying conditions: natural drying and convective drying. Convective drying took place in a convection chamber set at different temperatures (35 to 65 °C) and the process was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…It is important to point out that for the determination of a more precise value it would be necessary to define Def at more temperature values. Even so, the values of Def and Ea estimated in this study are consistent with values previously reported for other materials, considering their differences in composition, such as: grape seeds (4.36•10 -10 -6.82•10 -10 m 2 /s 2 and 11.29 to 12.83 kJ/mol) (Lozano et al, 2013), thistle flower (1.30•10 -9 -5.35•10 11 m 2 /s 2 and 56.48 kJ/mol) (Guiné et al, 2019) and beans (2.10•10 -10 -6.8•10 -10 m 2 /s 2 and 34.51 kJ/mol) (Silva et al, 2014) among others.…”
Section: Drying Of Cupuassu Almondssupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to point out that for the determination of a more precise value it would be necessary to define Def at more temperature values. Even so, the values of Def and Ea estimated in this study are consistent with values previously reported for other materials, considering their differences in composition, such as: grape seeds (4.36•10 -10 -6.82•10 -10 m 2 /s 2 and 11.29 to 12.83 kJ/mol) (Lozano et al, 2013), thistle flower (1.30•10 -9 -5.35•10 11 m 2 /s 2 and 56.48 kJ/mol) (Guiné et al, 2019) and beans (2.10•10 -10 -6.8•10 -10 m 2 /s 2 and 34.51 kJ/mol) (Silva et al, 2014) among others.…”
Section: Drying Of Cupuassu Almondssupporting
confidence: 92%
“…Mathematical modelling of drying curves: The moisture values obtained during drying were adjusted to mathematical models (Guiné et al, 2019;Ju et al, 2018;Reis et al, 2015;Silva et al, 2014;Silva et al, 2015) presented in Table 1 with the aid of LABfit software, version 7.2.50. The adjustment of the experimental data to the mathematical models was evaluated through the coefficient of variation (R²) and through the relative mean error, calculated by the expression: P (%) = [(experimental value -predicted value)/experimental value]•100%.…”
Section: Drying Curvesmentioning
confidence: 99%
“…Heat causes the breakdown of covalent bonds between phenolic compounds and the food matrix, leading to the improved extraction efficiency of phenolics [18,19]. However, phenolic compounds are often degraded after prolonged exposure to extreme heat [22], explaining the higher TPC observed in our pan-roasted seeds at 100 • C compared with vacuum oven-roasted seeds at 150 °C, using the same roasting time of 20 min. Among all the sacha inchi seed samples, the tray dryer-roasted seeds exhibited the lowest TPC at 10% lower than TPC in raw seeds.…”
Section: Discussionmentioning
confidence: 88%
“…The values of moisture in natura are very similar for the three chestnut samples, and the drying substantially decreased the moisture content to values around 5–6%. These values of the moisture of “castanha pilada” are suitable to guarantee that no degradation reactions occur, either of microbial, chemical or enzymatic nature [ 22 ].…”
Section: Resultsmentioning
confidence: 99%